Photochemical and photophysical behaviour of vitamin E: Interaction of its long-lived transient photoproducts with carotenoids - Naqvi, K. Razi; Melø, Thor Bernt; Sliwka, Hans Richard; Mohamad, Samsun Baharin; Partali, Vassilia (Royal Society of Chemistry, 2003)
Multi-channel, flash kinetic spectroscopy with microsecond time resolution has been used for investigating the interactions between carotenoids and the following photoproducts of α-tocopherol (EH) in hexane, methanol, acetonitrile, and dimethyl sulfoxide: (a) the lowest triplet, (b) the tocopherol radical cation, which could be seen only in the polar aprotic solvents acetonitrile and dimethyl sulfoxide, and (c) the neutral tocopheroxyl radical. The first two species reconvert to EH by transferring triplet excitation and positive charge (respectively) to the carotenoid; the third is unreactive. The relevance of these observations to photoprotection and the photoionisation of sterically hindered phenols is pointed out.